2010
DOI: 10.1264/jsme2.me10134
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Betaproteobacteria inside the Mycelium of the Fungus Mortierella elongata

Abstract: Microscopic and molecular analyses showed the presence of endobacteria inside the mycelia of four out of twelve nitrous oxide (N 2 O)-producing fungal isolates identified as Mortierella elongata. The 16S rRNA gene was successfully amplified with DNA extracted directly from the endobacterium-containing fungal strains and all sequences were related to that of Candidatus Glomeribacter gigasporarum in the family Burkholderiaceae. Bacterial endotoxin was detected in the endobacterium-positive fungal strains but onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 25 publications
4
78
2
Order By: Relevance
“…There is, however, increasing evidence that Mortierella species (Mucoromycotina) host endobacteria that are related to CaGg (Sato et al, 2010;Kai et al, 2012;Bonito et al, 2013). These data open a novel interesting scenario: fungal endobacteria might prefer coenocytic hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, increasing evidence that Mortierella species (Mucoromycotina) host endobacteria that are related to CaGg (Sato et al, 2010;Kai et al, 2012;Bonito et al, 2013). These data open a novel interesting scenario: fungal endobacteria might prefer coenocytic hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…One example of these microbial symbioses is that between plant-associated fungi and their bacterial endosymbionts (endobacteria, endofungal bacteria, or endohyphal bacteria [EHB]). Recent studies have indicated that EHB are widespread in rhizosphere fungi from diverse fungal phyla (e.g., mycorrhizal and pathogenic fungi from the Basidiomycota, Glomeromycota, and Mucoromycotina [6][7][8][9][10][11][12][13]) and in the highly diverse Ascomycota that infect roots, stems, and leaves as endophytes (14) (class 3 endophytes, sensu [15]). However, functional relationships have been studied for only a few associations, limiting inferences regarding the scope and potential importance of EHB-fungal associations in ecological interactions and human applications (but see references 16 and 17).…”
mentioning
confidence: 99%
“…Most studies aimed at understanding functional relationships between EHB and fungi have focused on root-associated fungi, especially arbuscular mycorrhizal fungi in the Glomeromycota and plant-pathogenic Rhizopus in the Mucoromycotina (6)(7)(8)(9)(10)(11)(18)(19)(20)(21)(22)(23). EHB in rhizosphere fungi are often vertically transmitted and host specific, and they frequently maintain obligate relationships with their hosts (18)(19)(20).…”
mentioning
confidence: 99%
“…increasing the fungal sporulation success and raising the fungal bioenergetics capacity (Salvioli et al 2016). Another well-studied example is the rice seedling Microscopic and molecular analysis showed that several nitrous oxide-producing fungal isolates of Mortierella elongata harboured endobacteria in their mycelia (Sato et al 2010). The sequencing of 16S rRNA genes revealed that the N 2 O-producing fungus…”
Section: Kotze 2010)mentioning
confidence: 99%
“…Mortierella elongate harbored endobacteria belonging to the family Burkholderiacea, however, the significance of this fungal-bacterial association is unknown (Sato et al 2010).…”
Section: Kotze 2010)mentioning
confidence: 99%